251 A POINT PREVALENCE STUDY OF FRAILTY IN ADULTS OVER THE AGE OF 75 IN A TERTIARY HOSPITAL. (18th November 2021) - Gannon, E; Cloney, T; Nor, N; Khan, I; Murphy, J; Plant, R; Murphy, D; Rafferty, M; O'Mahony, E; Stoneman, S; Creed, S; Byrne, E; et al.
Abstract: Background: Early identification and comprehensive assessment of frailty in older adult hospital inpatients is associated with improved outcomes. The aim of this study was to identify the prevalence of frailty amongst inpatients aged over 75 in a tertiary hospital. A secondary aim was to identify older adults inpatients who would have been better admitted under and managed by Geriatric Medicine services. Methods: Inpatients over the age of 75 were identified by a search of the electronic patient information system iPIMS on 26/08/2021. Patients attending a day service or needing Critical care were excluded. Information was collected using a paper questionnaire from patient records. Frailty was screened using the Think FRAIL tool. Data was stored on a password protected computer and analysed using Microsoft Excel. Results: 336 patients were initially identified from the electronic census. Following exclusion criteria 192 patients were included in data collection. Overall prevalence of frailty reached 89% (n = 171). New or worsening functional impairment was identified in 70% of patients (n = 135), altered mental status was present in 40% (n = 80). The Geriatric Emergency Medicine (Front Door Frailty) Service assessed 17% (n = 33) of patients. 31% (n = 59) of patients had a Comprehensive Geriatric Assessment. Inpatients under a Geriatric Medicine service accounted for 34% (n = 66). Of those not admitted under a Geriatric Medicine service (n = 151) 47% were identified as having needs better met by Geriatric Medicine admission. Conclusion: Slaintecare and ICPOP (Enhancec Community care) policies and guidance recommend early identification and assessment of older adults living with frailty to improve outcomes. We found a high prevalence of frailty in our inpatient population and a low % of early assessment. To implement 'Right care, right time, right place, given by the right team' policy we need to re-design our hospital services to meet needs of older adults in our hospitals. Geriatric Medicine must advocate for this at local and national level.